Effect of protective lung ventilation on pulmonary complications after laparoscopic surgery: a meta-analysis of randomized controlled trials - Sun, Menglin; Jia, Ruolin; Wang, Lijuan; Sun, Daqi; Wei, Mingqian; Wang, Tao; Jiang, Lihua; Wang, Yuxia; Yang, Bo (Frontiers in Medicine, 2023)
Introduction: Compared with traditional open surgery, laparoscopic surgery is widely used in surgery with the advantages of minimally invasive, good cosmetic effect, and short hospital stay, but in laparoscopic surgery, pneumoperitoneum and trendelenburg position may cause complications such as atelectasis. Recently, several studies have shown that the Protective Lung Ventilation Strategies are protective for abdominal surgery, reducing the incidence of PPCs. Ventilator-associated lung injury can be reduced by protective lung ventilation, which includes microtidal volume (4—8 mL/kg) ventilation and positive end-expiratory pressure (PEEP). Therefore, we used randomised controlled trials (RCTs) to assess the results of this topic, and RCTs were used for meta-analysis to further evaluate the effect of protective lung ventilation on pulmonary complications in patients undergoing laparoscopic surgery. Methods: In this meta-analysis, we searched the relevant literature contained in six major databases, CNKI, CBM, Wanfang Medical, Cochrane, PubMed, and Web of science, from their inception to October 15, 2022. After screening the eligible literature, a randomized controlled method was used to compare the occurrence of postoperative pulmonary complications when protective lung ventilation strategy and conventional lung ventilation strategy are applied to laparoscopic surgery. After statistical analysis, it was verified that the results were statistically significant. Results: Twenty-three trials were included. Patients receiving protective lung ventilation were 1.17 times less likely to develop pulmonary complications after surgery than conventional lung ventilation (hazard ratio [RR] 0.18, 95% confidence interval [CI] 1.13–1.22; I2 = 0%). Tested for bias (P = 0.36), it was statistically significant. Patients with protective lung ventilation are less likely to develop pulmonary complications after laparoscopic surgery. Conclusion：As a conventional form of ventilation, mechanical ventilation can easily cause ventilator-related lung injury and postoperative pulmonary complications. Therefore, we consider protective lung ventilation, which is effective in reducing the incidence of lung injury and lung infection. Implementing a low tidal volume + moderate end-expiratory positive pressure strategy reduces the risk of lung injury and lung infection. By optimizing ventilation parameters, the occurrence of complications such as pneumonia, atelectasis and lung injury is reduced.